2007
DOI: 10.1111/j.1551-2916.2007.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of V Substitution on Dielectric and Polarization Properties for Sr0.5Bi2.25Na1.25(Nb3−xVx)O12 Ceramics

Abstract: 1.25 (Nb 3Àx V x )O 12 ceramics were investigated in this study. From the X-ray powder diffraction results, no secondary phase was detected in the composition range of 0-0.075. The remanent polarizations (P r ) of the samples in the composition range of 0-0.03 were improved by the V substitution for Nb and the highest P r value of approximately 15 lC/cm 2 was obtained at x 5 0.03; it was noted that the V substitution for Nb was effective in improving the P r values in this ceramics. On the other hand, the coer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…When comparing the P r value of the sample at x = 0.03 with that of the sample at x = 0, the improvement in the P r value was recognized by the V substitution, though the remarkable differences in the E c values of the samples at x = 0 and 0.03 was not observed. In the case of small amount of V-substituted ferroelectric materials, it is reported that the ratting in the BO 6 octahedron in the [A n-1 B n O 3n+1 ] 2− perovskite block which relates with the structural distortion and the improvement in the sinterability enhances the ferroelectric properties of the materials [6,12]. The temperature dependences of dielectric constant of BSTVF at 1 MHz are shown in Fig.…”
Section: Lattice Parametersmentioning
confidence: 95%
See 2 more Smart Citations
“…When comparing the P r value of the sample at x = 0.03 with that of the sample at x = 0, the improvement in the P r value was recognized by the V substitution, though the remarkable differences in the E c values of the samples at x = 0 and 0.03 was not observed. In the case of small amount of V-substituted ferroelectric materials, it is reported that the ratting in the BO 6 octahedron in the [A n-1 B n O 3n+1 ] 2− perovskite block which relates with the structural distortion and the improvement in the sinterability enhances the ferroelectric properties of the materials [6,12]. The temperature dependences of dielectric constant of BSTVF at 1 MHz are shown in Fig.…”
Section: Lattice Parametersmentioning
confidence: 95%
“…As a result, the microstructure of BSTVF at x = 0.03 consists of fine grains of ∼6-10 µm as determined from the FE-SEM observations. The grain size of BSTVF at ceramics [6]. The microstructure analysis of BSTFV indicates that the small amounts of V substitution may effective in enhancing the grain growth of BSTFV.…”
Section: Lattice Parametersmentioning
confidence: 97%
See 1 more Smart Citation